A borrowing of bones - Munier, Paula (Munier, Paula. Mercy and Elvis mysteries, 2018)
"The first in a gripping new mystery series by literary agent Paula Munier, about a retired MP and bomb-sniffing dog who become embroiled in an investigation in the beautiful Vermont wilderness. It may be the Fourth of July weekend, but for retired soldier Mercy Carr and Belgian Malinois Elvis, it's just another walk in the remote Lye Brook Wilderness--until the former bomb-sniffing dog alerts to explosives and they find a squalling baby abandoned near a shallow grave filled with what appear to be human bones. U.S. Game Warden Troy Warner and his search-and rescue Newfoundland Susie Bear respond to Mercy's 911 call, and the four must work together to track down a missing mother, solve a cold-case murder, and keep the citizens of Vermont safe on potentially the most incendiary Independence Day since the American Revolution. A Borrowing of Bones is full of complex twists and real details about search-and-rescue dog training that Paula has learned through the training of her own dog. With its canine sidekicks and procedural plot, this series is well-positioned to become "Julia Spencer-Fleming with dogs" and will be a must-have for mystery fans" --